Development of AR-Based Educational Games for Mathematics Learning in Elementary Schools - Ruhiat Susanto; Mohammad Edy Nurtamam (Yayasan Adra Karima Hubbi, 2024)
The traditional approach to mathematics education in elementary schools often fails to engage students fully and can lead to a lack of interest in the subject. Augmented Reality (AR) technology presents a novel opportunity to enhance learning by integrating interactive, immersive experiences that can make mathematics more engaging and understandable for young learners. This study aims to develop and evaluate the effectiveness of AR-based educational games designed specifically for mathematics learning in elementary schools. The primary goal is to determine whether these games can improve students’ engagement and mathematical understanding compared to traditional teaching methods. A quasi-experimental design was employed, involving 150 elementary school students from three schools. Participants were divided into a control group, which continued with the standard curriculum, and an experimental group, which used the AR-based games. Data were collected through pre- and post-tests to assess mathematical understanding, as well as student engagement surveys. The findings revealed that students in the experimental group demonstrated significantly higher levels of engagement and improved test scores in mathematics compared to the control group. The AR games were particularly effective in enhancing students’ abilities to solve problems and understand complex mathematical concepts. The use of AR-based educational games in mathematics education can significantly enhance student engagement and understanding of the subject. This study suggests that incorporating AR technologies into the elementary school curriculum could be a beneficial strategy to revitalize mathematics education and improve learning outcomes.